Molecular characterization of segment 4 of lake tilapia viruses isolated from tilapia (Oreochromis niloticus) farmed in Peru - Palacios H., Shirley (2021)
The aim of this study was the molecular characterization of segment 4 of the lake tilapia virus (TiLV) detected in farmed tilapia from the departments of Piura (Coast) and San Martín (Jungle) in an outbreak that occurred in 2017-2018. During this outbreak, 26 TiLV positive samples were obtained and five of them were selected. The diagnosis of these samples was carried out through a nested RT-PCR with primers directed to segment 3 and the PCR products were sequenced. For the amplification and analysis of segment 4 of the TiLV genome, an RT-PCR was performed where specific primers were designed. The sequencing was done by Macrogen (South Korea), by bidirectional sequencing using the automated Sanger method. The phylogenetic analysis was carried out from the aligned sequences by means of the Neighbor-Joining (NJ) method and the hypothetical protein characteristics of the gene was carried out with the Phyre2 program. Four sequences with a length of 1190 bp were obtained and compared with two sequences from Israel and one from Thailand, reference strains corresponding to segment 4 of TILV published GenBank. The phylogenetic analysis of segment 4 determined the presence of a local TiLV genogroup, in addition to indicating that the Peruvian samples have a greater genetic relationship with the clade of Israel strains. The genetic distance analysis shows that the Peruvian samples have nucleotide identity values of 99.7-100% between them, determining that the outbreaks of both locations were produced by the same viral strain, and have an identity of 97.5-97.7% with strains from Israel and 97.0-97.1% with strains from Thailand. The hypothetical protein from TiLV segment 4 was determined to have structural homology to the neuraminidase N6 protein from English duck influenza A virus with 12% coverage, 44% identity, and 24.9% confidence.